Peran Responsiveness dan Usability Artificial Intelligent Chatbot Shopee terhadap Customer Satisfaction - Fathul Mahalli; Diqy Fakhrun Shiddieq; Dwi Nurhayati (Progresif: Jurnal Ilmiah Komputer, 2025)
The development of Artificial Intelligence (AI) has driven the adoption of chatbots in e-commerce, but this technology still faces challenges, especially in improving the quality of user interactions. The purpose of this study is to analyze the effect of Shopee chatbot responsiveness and usability on Customer Satisfaction. Using an explanatory quantitative approach, data was obtained from Shopee users through a Likert-scale questionnaire. The data was analyzed using SmartPLS 3.0. The analysis results prove that responsiveness and usability have a significant effect on customer satisfaction, having t-statistic values of 3.675 and 2.137, respectively. This finding confirms the importance of speed and ease of use of chatbots in increasing customer satisfaction. The novelty of this study lies in integrating both variables simultaneously and wider geographical coverage than previous studies. Practical implications include recommendations for developing chatbot features to support a superior shopping experience and maintain customer loyalty in the e-commerce industry.Keywords: Artificial Intelligence; e-commerce; Chatbot AbstrakPerkembangan Artificial Intelligence (AI) telah mendorong adopsi chatbot dalam e-commerce, namun teknologi ini masih menghadapi tantangan, khususnya dalam meningkatkan kualitas interaksi pengguna. Tujuan dari penelitian ini adalah untuk menganalisis pengaruh responsiveness dan usability chatbot Shopee terhadap Customer Satisfaction. Menngunakan pendekatan kuantitatif eksplanatori, data diperoleh dari pengguna Shopee melalui kuesioner berskala Likert. Data dianalisis menggunakan SmartPLS 3.0. Hasil analisis membuktikan bahwa responsiveness dan usability berpengaruh signifikan terhadap customer satisfaction, masing-masing memiliki nilai t-statistik 3,675 dan 2,137. Temuan ini menegaskan pentingnya kecepatan dan kemudahan penggunaan chatbot dalam meningkatkan kepuasan pelanggan. Kebaruan penelitian ini terletak pada pengintegrasian kedua variabel secara simultan dan cakupan geografis yang lebih luas dibandingkan penelitian sebelumnya. Implikasi praktis mencakup rekomendasi pengembangan fitur chatbot untuk mendukung pengalaman belanja yang unggul dan mempertahankan loyalitas pelanggan di industri e-commerce.Kata kunci: Artificial Intelligence; E-commerce; Chatbot